Telemedicine: A Literature Review on Ethical, Legal, and Social Issue (ELSI) - Permatasari, Gita; Basrowi, Ray Wagiu (The Indonesian Journal of Community and Occupational Medicine, 2023)
Introduction: In practice, telemedicine can be described as an activity or process of obtaining medical information with patients, or other clinical colleagues, without meeting in person. Ethical and medicolegal issues are widely know following in its implementation. Despite of that, telemedicine has several benefits. And because of this benefit, after the covid pandemic ended, telemedicine activities are still being carried out and favored by several types of patients. Therefore, a study is needed regarding the ethical, legal, and social issues related to telemedicine. Method: This study is a literature review related to telemedicine’s topic. Literature search was carried out on the pubmed and sciencedirect databases using keywords related to telemedicine. Literature included in the criteria will be reviewed and discussed following ethical, legal, and social issue (ELSI). Result: Most of 11 aspects of ethical, legal, and social issue (ELSI) are discussed in both of the literature such as : Quality of Care, Consent and Autonomy, Access to Care and Technology, Legal and Regulatory, Clinician Responsibilities, and Policy. 5 to 6 of these topic commented negatively in both literature, while only 4 topic commented positively. Conclusion: Both of these literatures provide information regarding the positive and negative aspects of teleconsulting. Even though negative comments and challenges related to ethical, legal, and social issues are discussed more, the positive aspects of telemedicine still exist and can be taken into account. The two studies encourage medical providers, government, clinical, patient, and other parties to establish a good telemedicine service.